Foreign ownership, tax preference and firm performance - Wunhong Su; Xiaobao Song; Chun Guo (Journal of Accounting, Business and Management (JABM), 2022)
Continuingly deepening reform, upgrading and transforming industries and attracting investment from foreign-funded firms become important measures to boost China's economic reform. Chinese government adopts various preferential tax policies for different industries since the beginning of the implementation of reform and opening-up. This study employs A-share listed firms from 2011 to 2017 as the sample to investigate the relation between foreign ownership, tax preference and firm performance. The results show that tax preference has positive relation with the investment of foreign-funded firms, and the investment and shareholding of foreign-funded firms have positive impact on the firm performance.